ARSITEKTUR EMPATI DAN INTERAKSI SOSIAL POSITIF SEBAGAI UPAYA PENCEGAHAN PERUNDUNGAN DI LINGKUNGAN SATUAN PENDIDIKAN - Asri, Ardison; Caesar Kusuma Atmaja, Aria; Sinaga, Maniur; Dzulkarnain, Ariefin; Cahyo Haryono, Yohanes (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
This study is based on the end of 2023 notes released by the Federation of Indonesian Teachers' Unions that the number of bullying cases in Indonesia reached 30 (thirty) cases that had been reported and processed by the authorities. Of that number, 80% occurred under the Ministry of Education, Culture, Research, and Technology and 20% of cases occurred in educational units under the Ministry of Religion, with the distribution of cases occurring at the junior high school/equivalent level as much as 50%, elementary school/equivalent as much as 30%, high school/equivalent as much as 20%. Even from a number of these cases, some cases have resulted in fatalities. Ironically, some of these bullying cases occurred in educational unit environments. Therefore, it is very interesting to study efforts to prevent bullying in educational unit environments through the approach of empathy architecture and positive social interaction. To answer these problems, a normative legal research method supported by empirical research was used. From the results of the study, it was found that the issue of school architecture is one of the triggers for bullying in the educational unit environment because bullying tends to occur in certain areas or places in the educational unit environment due to a lack of monitoring and supervision. However, bullying is not only caused by architectural factors but also social factors. The existence of positive social interactions where relationships between individuals are based on mutual respect, respect for differences, empathy, and cooperation that involve good relationships between students and students, students and teachers, and students with other school staff. When this continues to be developed, students feel accepted and appreciated, so they tend to be more confident and have a sense of belonging to the school.